2009
DOI: 10.1111/j.1748-0361.2009.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Do International Medical Graduates (IMGs) “Fill the Gap” in Rural Primary Care in the United States? A National Study

Abstract: IMGs fill gaps in the primary care workforce in many rural areas, but this varies widely between states. Policies aimed to redress the rural-urban physician maldistribution in the United States should take into account the vital role of IMGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 32 publications
0
56
2
Order By: Relevance
“…Furthermore, although many believe IMGs are more likely to practice in underserved settings, evidence does not clearly support this. 17,21,23,25,26 Finally, in recent years, the Public Service Loan Forgiveness (PSLF) program has become an important part of the workforce landscape. PSLF allows graduates who work for nonprofit organizations and make regular student loan payments for 10 years to have their remaining federal student debt forgiven.…”
mentioning
confidence: 99%
“…Furthermore, although many believe IMGs are more likely to practice in underserved settings, evidence does not clearly support this. 17,21,23,25,26 Finally, in recent years, the Public Service Loan Forgiveness (PSLF) program has become an important part of the workforce landscape. PSLF allows graduates who work for nonprofit organizations and make regular student loan payments for 10 years to have their remaining federal student debt forgiven.…”
mentioning
confidence: 99%
“…1 IMGs have historically contributed to the U.S. primary care workforce, 11,12 and, given the steady numbers of applicants for ECFMG certification over the past several years, 14 they are likely to continue to do so. Research into IMGs' demographics and practice characteristics-particularly the roles that different IMG groups play in primary care-could help inform U.S. physician workforce policies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Studies have shown IMGs to be more likely than USMGs to specialize in primary care disciplines 11 and to practice in rural areas. 12 In 2005-2006, 24.6% of all visits to office-based physicians were to IMGs. 11 The source countries of IMGs have been changing over time.…”
mentioning
confidence: 99%
“…Dill & Poll-Hunter, 2010;Shah et al, 2010). They are indispensable in providing primary healthcare in underserved areas (Kostis & Ahmad, 2004) and in regions where U.S. medical graduate (USMG) shortages are profound (Hagopian, Thompson, & Hart, 2004;Thompson, Hagopian, Fordyce, & Hart, 2009). In the foreseeable future, the U.S. public is likely to see an increasing dependence on IMGs in their medical care (Brotherton, Rockey, & Etzel, 2005;McMahon, 2004).…”
Section: Statement Of the Problemmentioning
confidence: 99%